Analysis Management of A Need People Crossing Bridge Facility (JPO) on Ahmad Yani Street Batam City - Edi Indra; Januarto Januarto; Reinold Palit (Budapest International Research and Critics University, 2022)
This study aims to determine the effectiveness of the use of pedestrian bridge facilities in Batam City. As we know that the increase in the volume of vehicles, it causes congestion on the streets in Batam City. busy in the morning when they go to work and school or in the afternoon when they come home from work or school. Pedestrian movement includes movements along roads, cutting roads, and intersections. As is common in many big cities, due to the demands of economic development, trade, and ease of service coverage for the community, public facilities such as hotels, shops, and so on are usually clustered in a certain area, because of the location of one building with another building spreads throughout the area, then one day pedestrians have to cross vehicular traffic to get to their destination. However, often the presence of such pedestrians at a certain level will result in sharp conflicts with the flow of vehicles resulting in traffic delays and high accident rates. This type of research is descriptive with the method used being a qualitative method. This research was carried out at the People's Crossing Bridge in Batam City, while the data collection technique in this study was a direct review method. Then the data was analyzed through three stages, namely calculation and data analysis, data presentation, and concluding.